Imaging features of intrahepatic cholangiocarcinoma mimicking a liver abscess: an analysis of 8 cases - Manrong Liu (BMC, 2021)
Abstract Background In rare cases, intrahepatic cholangiocarcinoma can present as a pyogenic liver abscess and are often misdiagnosed. This study aimed to analyze the imaging features of intrahepatic cholangiocarcinoma mimicking a pyogenic liver abscess. Methods The clinical data and imaging results of eight patients with pathologically confirmed intrahepatic cholangiocarcinoma mimicking a liver abscess were retrospectively collected. Results The mean age was 58 years with a range of 46–68 years. Fever and leukocytosis were present in six patients. All the eight lesions were a single mass. Air–liquid levels were present in two patients. Only one patient showed hepatic lobar atrophy and hepatic capsule retraction. The double target sign of liver abscess was not noticed in the CT/MRI images of all eight patients. The inner wall of the lesion was rough and irregular, with multiple dot/patchy and wall nodule enhancements. The abscess wall and the marginal parenchyma were supplied by the hepatic artery in four patients, and the intralesional arteries were rough and disrupted. Bile duct dilatation was seen adjacent to the lesion. In seven patients, diffusion-weighted images showed irregular patchy restricted diffusion in the marginal parenchyma of the necrotic area in addition to the prominent restricted diffusion in the necrotic area. Two patients with cholangiolithiasis showed patchy slight CT hypodensity, slight T1 hypointensity, slight T2 hyperintensity, and patchy delayed enhancement. Multiple lymph nodes enlargement in the hepatic hilar area and the retroperitoneal space were seen in five patients. Conclusion Intrahepatic cholangiocarcinoma mimicking a pyogenic liver abscess have unique imaging features and require careful image examination to avoid misdiagnosis.